Democracy between Spaces of Citizenship and Civic Competences: Two Explorations with Privileged Witnesses in Italian Context (Politeja, 2022)
The contribution analyses the results of two surveys carried out by the Italian team within the international project #ShareEU – Shaping of the European Citizenship in the Post-Totalitarian Societies. Reflections after 15 Years of EU Enlargement, on aspects of citizens’ beliefs and attitudes towards European integration, citizenship and civic competences, including the exploration of concepts such as totalitarianism/authoritarianism, democracy and “democratic life”. The results show that adults are concerned with equipping young people with skills and attitudes that will help them to think and act as citizens, advocates of a citizenship they believe in, preparing them, from the primary level of education, to play a vital role in becoming agents of change rather than simply passive observers of events. The capacity of education to succeed in building respect in individuals for fundamental human rights and the values of an ethic of citizenship is emphasised. Among the agencies, the school is confirmed as the leading institution capable of promoting a culture of citizenship that increases the likelihood that students can become citizens in their values and actions, thus avoid ing the risk of falling into disengagement and iniquity. Democracy seems to be the bearer of fundamental human and common values and is characterized as an effective approach to improve the quality of life, even if the basic question still remains that of how to teach it.